A comparative ergonomic study of work-related upper extremity musculo skeletal disorder among the unskilled and skilled surgical blacksmiths in West Bengal, India - Ghosh, Tirthankar (Medknow Publications & Media Pvt Ltd, 2011)
OBJECTIVE: The main aim of the study was to determine the nature and extent of work-related upper extremity musculoskeletal disorders (MSDs) and physiological stress among the blacksmiths involved in surgical instrument industry. MATERIALS AND METHODS: In the present investigation, 50 male blacksmiths of each skilled and unskilled groups of the forging section had been selected. For the symptom survey, a questionnaire on discomfort symptoms was performed. Repetitiveness of work and hand grip strength of both the groups were measured. RESULTS: It was revealed that upper limb MSD was a major problem among both group of blacksmith, primarily involving the hand, wrist, fingers, and shoulder. From this study it was found that 66% (33) skilled and 80% (40) unskilled blacksmith workers are feeling discomfort. The most commonly affected regions among the skilled and unskilled blacksmith workers were lower back (skilled 65% and unskilled 80%), neck (skilled 60% and unskilled 80%), and hand (skilled 50% and unskilled).